Pengabdian Kepada Masyarakat Melalui Penyuluhan Pemberian Makan Yang Tepat Pada Bayi Dan Dalam Upaya Pencegahan Stunting Di Bengkong Sadai Kota Batam - Suhaera Suhaera; Aprilya Sri Rachmayanti; Yunisa Friscia Yusri; Ghalib Syukrillah Syahputra (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
The prevalence of stunting is one of the biggest nutritional problems among toddlers in Indonesia. The proportion of short and very short nutritional status in babies under two years old (baduta) reached 29.9% or higher than the 2019 RPJMN target, which was 28%. Stunting due to malnutrition that occurs in the First 1000 Days of Life (HPK) notonly causes obstacles to physical growth and increases vulnerability to disease, but also threatens cognitive development which will affect children's intelligence and productivity levels.Objective: To know the nutritional status of children under five, especially related to stunting, to increase parents' knowledge about stunting, to raise public awareness of the dangers of stunting.The activities consist of preparation stages, implementation of counseling which begins with filling in the pre-test questionnaire and ends with filling in the post-test questionnaire, as well as the evaluation stage.